ANALYSIS OF THE VARIABILITY AND THE SPECTRUM OF PERIODS OF EXTRAGALACTIC SOURCE OJ 287 IN THE RADIO WAVES - Donskykh, A.; Ryabov, M.; Suharev, A.; Aller, M. (Одеські астрономічні публікації, 2013)
We analyzed long-term monitoring of data flux of extragalactic source OJ 287 obtained at frequencies of 1GHz (1974-2011), 8 GHz (1971-2011), 4.8GHz and (1979-2010), on the RT-26,University of Michigan,USA. Variability of the flux of the radio source was investigated by applying wavelet analysis. There were identified long-period (in the range of 3.6 to 13.6 years) and short (in the range from 1.2 to 1.8 years) components at all studied frequencies and it was determined the time of their existence. The "spectra periods" for each year of observation were built to assess the contribution of individual periods in the formation of the most powerful phase of activity of the radio source. The dynamics of the manifestations of active periods at different frequencies was observed. The obtained data was compared with the results of MOJAVE VLBI monitoring for the period of 1995-2012 years at a frequency of 15.4 GHz. It allowed to investigate the structure of emissions during periods of manifestation activity maxima.